Synthesis and Characterizations of Biobased Copolymer Poly(ethylene-co-butylene 2,5-Furandicarboxylate) - Nam Vu Trung; Mai Ngoc Nguyen; Anh Nguyen Thi Ngoc; Ni Pham Thi; Tung Tran Quang; Thuy Tran Thi (International Journal of Polymer Science)
Homopolymers and copolymers derived from 2,5-furandicarboxylic acid have been extensively studied for their potential in the development of sustainable plastics. This research definitely spotlighted the synthesis of poly(ethylene-co-butylene 2,5-furandicarboxylate) copolymer via the two-step melting polycondensation with various ethylene glycol/1,4-butanediol molar ratios. The structural characterization of the obtained biobased copolymer was carried out by ATR-FTIR and 1H NMR. The average molecular weight of the obtained copolymer was determined by the intrinsic viscosity measurements. It was found that ethylene glycol was preferentially incorporated into the copolymer structures when the molecular weight of the products was not high enough (>18000). The decomposition of two types of monomer units of the obtained copolymer was proven through the degradation two-step process by TGA measurements.